Severe Bloodstream Infection due to KPC-Producer E coli in a Renal Transplant Recipient Treated With the Double-Carbapenem Regimen and Analysis of In Vitro Synergy Testing: A Case Report. Issue 7 (February 2016) - Oliva, Alessandra; Cipolla, Alessia; Gizzi, Francesca; D'Abramo, Alessandra; Favaro, Marco; De Angelis, Massimiliano; Ferretti, Giancarlo; Russo, Gianluca; Iannetta, Marco; Mastroianni, Claudio M.; Mascellino, Maria T.; Vullo, Vincenzo
Abstract : Abstract: Transplant recipients are at high risk of infections caused by multidrug resistant microorganisms. Due to the limited therapeutic options, innovative antimicrobial combinations against carbapenem-resistant Enterobacteriaceae causing severe infections are necessary. A 61-year-old woman with a history of congenital solitary kidney underwent renal transplantation. The postoperative course was complicated by nosocomial pneumonia due to Stenotrophomonas maltophilia and pan-sensitive Escherichia coli, successfully treated with antimicrobial therapy. On postoperative day 22, diagnosis of surgical site infection and nosocomial pneumonia with concomitant bacteremia due to a Klebisella pneumoniae carbapenemase-producer E coli was made. The patient was treated with the double-carbapenem regimen (high dose of meropenem plus ertapenem) and a potent synergistic and bactericidal activity of this un-conventional therapeutic strategy was observed in vitro. Despite a microbiological response with prompt negativity of blood cultures, the patient faced a worse outcome because of severe hemorrhagic shock. The double-carbapenem regimen might be considered as a rescue therapy in those subjects, including transplant recipients, in whom previous antimicrobial combinations failed or when colistin use might be discouraged. Performing in vitro synergy testing should be strongly encouraged in cases of infections caused by pan-drug resistant strains, especially in high-risk patients.